Aqueous organosilicon resin based on hydrophilic self-consuming groups and tetraethyl orthosilicate and a method for its preparation

CN122941004APending Publication Date: 2026-10-20CHANGZHOU JIANUO ORGANIC SILICON
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611101685.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]第一,TEOS易引发暴聚导致凝胶化,例如,CN201310369278.1公开了含硅酸酯的水性纳米树脂制备方法,但存在的问题是TEOS分子结构中含有四个极活泼的乙氧基,在加水水解时,易迅速形成多硅烷醇并发生不可控的三维网状缩聚

Benefits of technology

[0021](1)本发明利用二苯基硅二醇与正硅酸乙酯进行预缩聚,利用苯基的空间位阻,可降低后续加水时的局部交联速率,使得高含量正硅酸乙酯水性树脂在室温下储存12个月以上不凝胶。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a method for preparing waterborne organosilicon resin based on tetraethyl orthosilicate (TES) with hydrophilic self-consuming groups, belonging to the field of waterborne coating technology. The invention first reacts aminosilane with propylene carbonate to generate a hydrophilic silane monomer containing secondary hydroxyl groups; then, TES is subjected to anhydrous de-alcoholization prepolymerization with diphenylsilanediol; subsequently, the prepolymer is mixed with the hydrophilic silane monomer and methyltriethoxysilane, and co-hydrolyzed and polycondensed at pH 3.5-4.5, followed by de-alcoholization and phase inversion to obtain a microemulsion. This invention solves the problem of easy gelation of high-content TES in aqueous systems, resulting in excellent emulsion storage stability. Furthermore, when the resin forms a film and cures at 150-180℃, the secondary hydroxyl groups act as crosslinking sites, undergoing dehydration and polycondensation, causing the hydrophilic groups to be consumed in situ and transformed into a hydrophobic network. The final coating exhibits a hardness of 4H-5H and good water resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waterborne coatings and polymer resin synthesis technology, specifically to the preparation of waterborne organosilicon resins based on tetraethyl orthosilicate and the preparation method thereof. Background Technology

[0002] Organosilicon resins, with their Si-O-Si main chain, possess excellent high-temperature resistance, weather resistance, and chemical resistance, and are widely used in anti-corrosion, insulation, and high-temperature resistant coatings. With increasingly stringent global environmental regulations, reducing volatile organic compound (VOC) emissions has become an industry consensus, and the water-based formulation of organosilicon coatings has become a current hot topic in the polymer resin field.

[0003] In the synthesis system of organosilicon resins, tetraethyl orthosilicate (TEOS) serves as a precursor providing tetrafunctional groups, which can increase the crosslinking density of the resin. If TEOS can be effectively introduced into an aqueous system, it can impart waterborne coatings with a hardness of 4H or higher, abrasion resistance, and strong adhesion.

[0004] Currently, the following technical problems exist in introducing TEOS into waterborne resins and achieving waterborne application:

[0005] First, TEOS is prone to rapid polymerization leading to gelation. For example, CN201310369278.1 discloses a method for preparing aqueous nano-resins containing silicate esters, but the problem is that the TEOS molecule contains four highly reactive ethoxy groups, which readily form polysilanols and undergo uncontrolled three-dimensional network condensation during hydrolysis. Under conventional mixed co-hydrolysis processes, if the proportion of TEOS added to the aqueous system is slightly high, the emulsion will gel due to excessive local cross-linking during the water addition reaction stage or the initial stage of room temperature storage, resulting in the scrapping of the entire reactor. To avoid gelation, existing technologies often have to drastically reduce the amount of TEOS used, which results in a softer aqueous silicone coating that is difficult to meet the hardness requirements of heavy-duty industrial anti-corrosion or wear-resistant coatings.

[0006] Secondly, due to the hydrophobic nature of pure silicone resins, existing technologies typically employ two approaches to achieve stable dispersion in water: one is to add a large amount of surfactant; the other is to introduce hydrophilic monomers, such as polyether-modified silanes, polycarboxylic acid silanes, or polysulfonates, into the silicone backbone through chemical copolymerization. Currently, polyether silanes are widely used to provide hydrophilic balance, resulting in good emulsion storage stability of the resin. However, these traditional hydrophilic groups, such as the polyether segment -COC- or carboxylic acid groups, remain in the paint film network after high-temperature curing. This leads to waterborne paint films exhibiting problems such as water absorption, whitening, blistering, and peeling in long-term immersion or high-humidity environments, resulting in decreased water resistance and corrosion resistance. This poor water resistance due to hydrophilicity is a major obstacle preventing waterborne silicones from replacing solvent-based silicones.

[0007] Therefore, the technical problem to be solved by the present invention is how to add a large amount of tetraethyl orthosilicate to waterborne organosilicon resin without initiating gelation, so as to achieve emulsion storage stability and high hardness coating, and make the waterborne organosilicon coating have good water resistance. Summary of the Invention

[0008] To address the problems in the background art, this invention provides a method for preparing waterborne organosilicon resin based on self-consuming hydrophilic groups using tetraethyl orthosilicate. This invention solves the technical problem of easy gelation of high-content tetraethyl orthosilicate in aqueous systems, and the hydrophilic groups are consumed in situ during resin curing to form a film, so that the coating has excellent hardness, flexibility and water resistance that meet the requirements.

[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0010] (1) Add aminoalkyltrialkoxysilane and cyclic carbonate to a reactor and react at 60~80℃ for 4~8 hours. After the reaction, a hydrophilic silane monomer is prepared.

[0011] (2) Under anhydrous conditions, tetraethyl orthosilicate, diarylsilanediol and catalyst are mixed and reacted at 80~110℃ for 3~6 hours. The prepolymer is obtained by de-alcoholization polycondensation.

[0012] (3) Add the hydrophilic silane monomer and methyltriethoxysilane prepared in step (1) to the prepolymer obtained in step (2), mix them evenly, adjust the pH of the system to 3.5~4.5 with acid, and then add deionized water dropwise at 50~70℃ to carry out hydrolysis-co-condensation reaction for 2~4 hours; the molar amount of deionized water added is 1.2~1.8 times the total molar amount of tetraethyl orthosilicate, methyltriethoxysilane and hydrophilic silane monomer;

[0013] (4) Remove the alcohol byproducts generated in the reaction by vacuum distillation of the reaction solution in step (3); then cool the reaction system to 20~30℃, and slowly add deionized water dropwise under high-speed shearing and stirring at 1200~2500 r / min to carry out phase inversion, thus obtaining the waterborne organosilicon resin prepared by microemulsion tetraethyl orthosilicate.

[0014] (5) The above-mentioned water-based organosilicon resin is coated on the surface of the substrate. After being dried at room temperature, it is cured at a high temperature of 150~180℃ for 20~40 minutes to allow the secondary hydroxyl groups and siloxane groups to undergo dehydration condensation polymerization, thereby obtaining a high-hardness and water-resistant organosilicon coating.

[0015] Further, in step (1), the aminoalkyltrialkoxysilane is preferably γ-aminopropyltriethoxysilane (APTES); the cyclic carbonate is preferably propylene carbonate; the molar ratio of the two is 1:1 to 1:1.05;

[0016] Further, in step (2), the diarylsilanediol is preferably diphenylsilanediol, and the molar ratio of tetraethyl orthosilicate to diarylsilanediol is 1:0.5 to 1:4. The catalyst is at least one of organotin catalysts or titanate catalysts, and the amount of catalyst used is 0.05% to 0.5% of the sum of the mass of tetraethyl orthosilicate and diarylsilanediol in step (2).

[0017] Furthermore, in step (3), in molar amounts, tetraethyl orthosilicate is 10-30 parts, diarylsilanediol is 20-50 parts, methyltriethoxysilane is 30-60 parts, and hydrophilic silane monomer is 10-25 parts.

[0018] Furthermore, in step (3), the acid used to adjust the pH is selected from glacial acetic acid or formic acid.

[0019] Furthermore, after the phase inversion by adding deionized water, the solid content of the resulting aqueous organosilicon resin microemulsion is controlled to be 30%~45%.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] (1) In this invention, diphenylsilanediol and tetraethyl orthosilicate are prepolymerized. By utilizing the steric hindrance of the phenyl group, the local crosslinking rate during subsequent water addition can be reduced, so that the high-content tetraethyl orthosilicate waterborne resin does not gel when stored at room temperature for more than 12 months.

[0022] (2) This invention uses γ-aminopropyltriethoxysilane and propylene carbonate to react and obtain a hydrophilic silane monomer containing secondary hydroxyl and urethane groups. In the aqueous phase, it can provide hydrogen bond self-emulsification; in the high-temperature curing stage of 150~180℃, based on the principle of siloxane condensation, the active secondary hydroxyl groups will act as cross-linking curing sites and undergo dehydration condensation with the siloxane groups of the system. The hydrophilic groups are consumed in situ and a hydrophobic Si-OC three-dimensional network is generated, which improves the cross-linking density and water resistance of the coating film.

[0023] (3) The present invention uses propylene carbonate to replace the traditional toxic isocyanate to prepare polyurethane segments, achieving zero-toxicity production and extremely low VOC emissions, and the process is green and environmentally friendly. Detailed Implementation

[0024] Description of the detection method in the embodiment:

[0025] Film hardness: Tested according to GB / T 6739-2006 "Determination of film hardness by pencil method".

[0026] Adhesion test: The test was conducted in accordance with GB / T 9286-2021 standard "Cross-cut test for paints and varnishes".

[0027] Butyl ketone (MEK) wiping test: According to GB / T 23989-2009 standard, absorbent cotton soaked in MEK solvent is used to repeatedly wipe the paint film surface under a 1kg load. The number of wipings when the substrate is exposed or damaged is recorded. The higher the number of wipings, the denser the cross-linking.

[0028] Water immersion resistance and water absorption rate: The test was conducted according to GB / T 1733-1993 "Test Method for Water Resistance of Coating Film", and the state of the coating film was observed after immersion in water for 30 days; the water absorption rate was taken as the percentage increase in film weight after immersion in deionized water for 24 hours.

[0029] Water droplet contact angle: An optical contact angle meter was used, and the test liquid was deionized water with a droplet volume of 3 μL.

[0030] Storage stability: Storage stability is tested by sealing and standing at room temperature and observing whether stratification, precipitation or gelation occurs.

[0031] Paint film preparation: carried out in accordance with GB / T 1727-2021 "General method for preparing paint film".

[0032] Example 1

[0033] (1) In a 500 mL four-necked flask equipped with a condenser and a stirrer, add 22.1 g (0.1 mol) of γ-aminopropyltriethoxysilane (APTES, purity ≥98%, commercially available) and 10.2 g (0.1 mol) of propylene carbonate (PC, purity ≥99%, commercially available). Purge the air three times with nitrogen gas of 99.9% purity, raise the temperature to 70 °C and stir for 6 hours. After the reaction is complete, a pale yellow transparent viscous liquid is obtained, which is the hydrophilic silane monomer (HUS) containing a carbamate structure and a secondary hydroxyl group, with a yield of 98.5%.

[0034] (2) In another dry 1000mL four-necked reactor, 41.6g (0.2 mol) of tetraethyl orthosilicate (TEOS, purity ≥98%, commercially available) and 64.8g (0.3 mol) of diphenylsilanediol (DPDS, purity ≥98%, commercially available) were added, followed by 0.1g of tetraisopropyl titanate as a catalyst. The temperature was raised to 100℃ under nitrogen protection and the reaction was maintained for 4 hours. During this period, the ethanol produced by the dealcopolymerization was collected by distillation apparatus to obtain a transparent and viscous prepolymer.

[0035] (3) Lower the reactor temperature to 60°C, and add all of the HUS monomers (0.1 mol) prepared in step (1) and 71.2 g (0.4 mol) of methyltriethoxysilane (MTES, purity ≥98%, commercially available) to the product of step (2) in sequence, and stir until homogeneous. Adjust the pH of the system to 4.0 with 0.1 mol / L glacial acetic acid aqueous solution. Then, at 60°C, add 18.0 g (1.0 mol) of deionized water dropwise over 1.5 hours using a dropping funnel. After the addition is complete, continue to maintain the temperature for co-condensation for 3 hours. The system remains transparent to slightly blue, and no gel particles are generated.

[0036] (4) Distill under reduced pressure at 50℃ and a vacuum of -0.09MPa to remove free ethanol and some water from the system until no distillate flows out. Stop vacuuming, cool to 25℃, and slowly add 200g of deionized water dropwise over 1 hour at a high-speed shear of 1500 r / min. The system undergoes phase inversion to obtain an aqueous organosilicon microemulsion with a solid content of about 42%.

[0037] (5) Curing, crosslinking, and performance testing:

[0038] The above-mentioned aqueous silicone microemulsion was coated onto a standard tinplate (150mm×70mm×0.3mm), with the wet film thickness controlled at approximately 60μm and the dry film thickness at approximately 27μm. After surface drying at room temperature, it was cured in a 180℃ forced-air oven for 30 minutes to obtain a high-hardness and water-resistant silicone coating.

[0039] Example 2

[0040] The difference between Example 2 and Example 1 lies only in the amount of raw materials added in step (2). Specifically, the amount of tetraethyl orthosilicate was adjusted to 62.4 g (0.3 mol), the amount of diphenylsilanediol was adjusted to 43.2 g (0.2 mol), and the molar ratio of TEOS to DPDS was 1.5:1. Other operations were the same as in Example 1, and an aqueous organosilicon microemulsion was prepared. After curing under the same conditions, it was tested.

[0041] Example 3

[0042] The difference between Example 3 and Example 1 lies in the amount of raw materials added in step (2). Specifically, the amount of tetraethyl orthosilicate is adjusted to 20.8 g (0.1 mol), the amount of diphenylsilanediol is adjusted to 86.4 g (0.4 mol), and the molar ratio of TEOS to DPDS is 1:4. Other operations are the same as in Example 1. An aqueous organosilicon microemulsion is prepared, cured under the same conditions, and then tested.

[0043] Example 4

[0044] The difference between Example 4 and Example 1 lies in the different feeding ratios in step (3). Specifically, the raw materials are fed in the following molar proportions: 30 parts TEOS, 20 parts DPDS, 40 parts MTES, and 10 parts HUS (corresponding mass: 62.4g TEOS, 43.2g DPDS, 71.2g MTES, and 22.1g HUS). Other operations are the same as in Example 1. An aqueous silicone microemulsion is prepared, cured under the same conditions, and then tested.

[0045] Example 5

[0046] The difference between Example 5 and Example 1 lies in the curing temperature in step (5): the curing temperature was adjusted to 150°C, and the curing time was 40 minutes. Other operations were the same as in Example 1, and the coating was tested after preparation. Comparative Example 1 (no pre-polymerization, direct co-hydrolysis)

[0047] Compared with Example 1, Comparative Example 1 omits the pre-condensation step (2) and directly mixes tetraethyl orthosilicate and diphenylsilanediol with the HUS monomer and MTES prepared in step (1) for co-hydrolysis:

[0048] (1) Prepare HUS monomer, same as step (1) in Example 1;

[0049] (2) In a 1000 mL reactor, add 41.6 g (0.2 mol) tetraethyl orthosilicate, 64.8 g (0.3 mol) diphenylsilanediol, all of the HUS monomers obtained in step (1) (0.1 mol), and 71.2 g (0.4 mol) methyltriethoxysilane. After mixing thoroughly, adjust the pH to 4.0 with 0.1 mol / L glacial acetic acid and heat to 60 °C. Then, start adding 18.0 g of deionized water dropwise for co-hydrolysis.

[0050] In Comparative Example 1, approximately 30 minutes after the addition of deionized water, the reaction solution in the reactor rapidly turned white and released heat, with a large amount of white insoluble resin lumps appearing. The reaction system gelled and became unusable, making subsequent testing impossible.

[0051] Comparative Example 2 (using polyether-modified silane instead of HUS)

[0052] The process steps are the same as in Example 1, except that in step (3), the HUS monomer prepared in step (1) is replaced with an equimolar amount of polyether-modified triethoxysilane (commercially available, molecular weight approximately 450, containing approximately 7 EO units, 0.1 mol, 45.0 g) as a hydrophilic chain extender. The remaining operations are the same as in Example 1. After the aqueous silicone microemulsion is prepared, it is cured under the same conditions and then tested.

[0053] Comparative Example 3 (using dimethylsilanediol instead of diphenylsilanediol)

[0054] The difference between Comparative Example 3 and Example 1 is that in step (2), 64.8 g (0.3 mol) of diphenylsilanediol was replaced with an equimolar amount (27.7 g, 0.3 mol) of dimethylsilanediol, while other operations were the same as in Example 1. In the latter half of the hydrolysis process in step (3) of Comparative Example 3 (approximately 1 hour after adding deionized water), the viscosity of the system increased significantly, the stirring resistance increased, and it crosslinked into a jelly-like gel within the following 20 minutes, making subsequent phase inversion dispersion and coating detection impossible.

[0055] Comparative Example 4 (HUS dosage too low)

[0056] The process steps of Comparative Example 4 are the same as those of Example 1, except that in steps (1) and (3), the amount of HUS monomer is halved to 0.05 mol (approximately 11.0 g in mass), and the other operations are the same as those of Example 1.

[0057] Due to insufficient number of hydrophilic groups, in Comparative Example 4, during the high-speed shearing and water phase conversion in step (4), water droplets could not easily enter the hydrophobic siloxane network and could not form a stable microemulsion. After stirring stopped, obvious oil-water separation occurred, making it impossible to conduct subsequent coating tests.

[0058] Comparative Example 5 (excessive HUS dosage)

[0059] The process steps of Comparative Example 5 are the same as those of Example 1, except that in steps (1) and (3), the amount of HUS monomer is increased to 0.35 mol (approximately 77.4 g in mass), and the other operations are the same as those of Example 1.

[0060] Although an emulsion can be formed, excessive residual hydrophilic segments lead to a deterioration in coating performance. Tests were conducted under the same curing conditions, and the results are shown in Table 1.

[0061] Comparative Example 6

[0062] Comparative Example 6 uses the same process as Steps (1)-(4) of Example 1 to prepare an aqueous organosilicon microemulsion, the only difference being the film-forming curing conditions: the microemulsion obtained in Example 1 is coated on the surface of the substrate, dried naturally at room temperature and cured for 7 days to obtain a room temperature cured paint film, and then the performance is tested.

[0063] Comparative Example 7

[0064] Compared with Example 1, Comparative Example 7 differs in that: in step (1), the hydrophilic silane monomer HUS is not prepared, but 1,2-propanediol of the same mass as the hydrophilic monomer in Example 1 is added directly in step (3) as a hydrophilic agent for physical mixing.

[0065] (1) In a dry 1000 mL four-necked reactor, 41.6 g (0.2 mol) of tetraethyl orthosilicate (TEOS) and 64.8 g (0.3 mol) of diphenylsilanediol (DPDS) were added, followed by 0.1 g of tetraisopropyl titanate as a catalyst. The mixture was heated to 100 °C under nitrogen protection and kept at that temperature for 4 hours. During the reaction, the ethanol produced by the dealcopolymerization was collected by distillation to obtain the prepolymer.

[0066] (2) Lower the reactor temperature to 60°C, and add 71.2 g of methyltriethoxysilane and 32.3 g of 1,2-propanediol to the prepolymer product sequentially, stirring until homogeneous. Adjust the pH of the system to 4.0 with 0.1 mol / L glacial acetic acid aqueous solution. Then, at 60°C, add 18.0 g of deionized water dropwise over 1.5 hours using a dropping funnel. After the addition is complete, continue to maintain the temperature for co-condensation for 3 hours. The system remains transparent to slightly blue, with no gel particles generated.

[0067] (3) Perform vacuum distillation, removing free ethanol from the system at 50℃ and a vacuum of -0.09MPa until no fraction flows out. Stop vacuuming, cool to 25℃, and slowly add 200g of deionized water dropwise over 1 hour at a high-speed shear rate of 1500 r / min. The system undergoes phase inversion to obtain an aqueous organosilicon microemulsion.

[0068] (4) The aqueous silicone microemulsion is coated onto the surface of the substrate, and after being dried at room temperature, it is cured at 180°C for 30 minutes to obtain the coating.

[0069] Comparative Example 8

[0070] Comparative Example 8 differs from Example 1 only in that, in step (1), propylene carbonate is replaced with an equimolar amount of ethylene carbonate, thereby preparing a hydrophilic silane monomer containing a primary hydroxyl group. The specific operation is as follows:

[0071] (1) In a 500 mL four-necked flask equipped with a condenser and a stirrer, add 22.1 g (0.1 mol) of γ-aminopropyltriethoxysilane (APTES) and 8.8 g (0.1 mol) of ethylene carbonate (EC). Purge the air with nitrogen gas of 99.9% purity, heat to 70 °C and stir for 6 hours to prepare a hydrophilic silane monomer for later use;

[0072] (2) In another dry 1000mL four-necked reactor, 41.6g (0.2 mol) tetraethyl orthosilicate and 64.8g (0.3 mol) diphenylsilanediol were added, followed by 0.1g tetraisopropyl titanate. The mixture was heated to 100℃ under nitrogen protection and reacted for 4 hours. The distillate was collected to obtain the prepolymer.

[0073] (3) Lower the reactor temperature to 60°C, and add the hydrophilic silane monomer prepared in step (1) and 71.2 g (0.4 mol) methyltriethoxysilane to the product of step (2) in sequence, and stir until homogeneous. Adjust the pH of the system to 4.0 with 0.1 mol / L glacial acetic acid aqueous solution. Then, at 60°C, start adding 18.0 g of deionized water dropwise for co-hydrolysis and polycondensation.

[0074] During the addition of deionized water in step (3), as the co-condensation of the reaction system proceeds, under acidic co-hydrolysis conditions at 60°C, the primary hydroxyl groups, due to their high reactivity, prematurely hydrolyze with tetraethyl orthosilicate and methyltriethoxysilane, resulting in dehydration and crosslinking. Approximately 45 minutes into the water droplet, the system viscosity increases, making stirring difficult. Within the following 10 minutes, it crosslinks into an irreversible white three-dimensional network gel, making subsequent phase inversion dispersion and coating detection impossible.

[0075] After the above embodiments and comparative examples were cured under the specified conditions, the performance test results are shown in Table 1:

[0076] Table 1:

[0077]

[0078] (1) Comparative Example 1 omitted the pre-condensation step of diphenylsilanediol and tetraethyl orthosilicate, and all silane monomers were mixed at once and then co-hydrolyzed. The system gelled rapidly after being dropped with water. In contrast, Example 1 reduced the hydrolysis condensation rate of the tetrafunctional silane by pre-de-alcoholizing TEOS and DPDS, utilizing the steric hindrance effect of the phenyl group, thus allowing the subsequent co-hydrolysis to proceed smoothly. This comparison confirms the key role of the pre-condensation step in inhibiting the gelation of the high-TEOS content system.

[0079] (2) In Comparative Example 3, dimethylsilanediol without phenyl substitution was used instead of diphenylsilanediol for prepolymerization, and gelation still occurred in the later stage of co-hydrolysis. This indicates that the steric hindrance of phenyl groups is a key structural factor in inhibiting excessive crosslinking. Simply relying on prepolymerization without introducing steric hindrance groups cannot fundamentally solve the gelation problem of high TEOS content.

[0080] (3) The comparison between Example 1 and Comparative Example 6 shows that the water absorption rate of the paint film under room temperature curing is as high as 6.8%, and it turns white and bubbles after being soaked in water for 3 days; however, after baking at 180℃, the water absorption rate drops to 0.6%, and the water resistance reaches more than 30 days, and the number of MEK wipes increases from 60 times to >200 times. Comparative Example 7 adds small molecule 1,2-propanediol as a hydrophilic agent. Although it can assist in emulsification in the early stage, due to its lack of siloxane groups, the hydroxyl groups are difficult to chemically bond with the resin network during curing. Most of them remain in the paint film in the form of small molecules, resulting in a water absorption rate as high as 7.2% and poor water resistance.

[0081] (4) In Comparative Example 8, ethylene carbonate was used instead of propylene carbonate to prepare the HUS monomer. Since the primary hydroxyl group formed after ring-opening prematurely participated in the polycondensation reaction in the co-hydrolysis system with TEOS / MTES, cross-linking and gelation occurred during the co-hydrolysis stage. In contrast, the secondary hydroxyl group formed after ring-opening of propylene carbonate exhibited moderate reactivity and remained stable during the co-hydrolysis stage, only participating in the cross-linking reaction during the high-temperature curing stage, thus achieving controllable timing of the hydrophilic-hydrophobic conversion. This indicates that the choice of propylene carbonate is one of the key factors in achieving the "self-consumption" function of this invention.

[0082] (5) Insufficient HUS dosage leads to insufficient hydrophilicity, making it impossible to achieve stable phase transformation and water-based coating; excessive HUS dosage, although it can emulsify, results in excessive hydrophilic chain residues, leading to a coating water absorption rate as high as 12.4%, complete loss of adhesion, and a hardness of only 1H. This indicates that the HUS dosage needs to be within the preferred range of 10 to 25 parts to balance the emulsification ability and the water resistance of the final coating.

[0083] (6) When Example 5 was cured at 150°C, the hardness, MEK wiping times and water resistance decreased slightly compared with those cured at 180°C, but were still better than those cured at room temperature. This indicates that 150°C is sufficient to initiate the cross-linking condensation reaction of the secondary hydroxyl groups, while 180°C can make the cross-linking more complete and achieve the best performance.

[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing waterborne organosilicon resin based on tetraethyl orthosilicate with hydrophilic self-consuming groups, characterized in that, Includes the following steps: (1) Mix aminoalkyltrialkoxysilane and cyclic carbonate in a molar ratio of 1:1 to 1:1.05 and react at 60 to 80°C for 4 to 8 hours to obtain a hydrophilic silane monomer containing a secondary hydroxyl group; (2) Under anhydrous conditions, tetraethyl orthosilicate, diarylsilanediol and catalyst are mixed and reacted at 80~110℃ for 3~6 hours to carry out de-alcoholization polycondensation to obtain a prepolymer; the molar ratio of tetraethyl orthosilicate to diarylsilanediol is 1:0.5~1:

4. (3) Add the hydrophilic silane monomer and methyltriethoxysilane prepared in step (1) to the prepolymer obtained in step (2), mix evenly, adjust the pH of the system to 3.5~4.5 with acid, and then add deionized water dropwise at 50~70℃ to carry out hydrolysis co-condensation reaction for 2~4 hours; the molar amount of the added deionized water is 1.2~1.8 times the total molar amount of tetraethyl orthosilicate, methyltriethoxysilane and hydrophilic silane monomer; (4) Remove the by-product alcohols by vacuum distillation of the reaction solution after hydrolysis co-condensation in step (3), then cool the reaction, and add deionized water dropwise under high speed shear stirring to carry out phase inversion, thereby obtaining waterborne organosilicon resin.

2. The preparation method according to claim 1, characterized in that, In step (1), the aminoalkyltrialkoxysilane is γ-aminopropyltriethoxysilane or γ-aminopropyltrimethoxysilane; the cyclic carbonate is propylene carbonate.

3. The preparation method according to claim 1, characterized in that, In step (2), the diarylsilanediol is diphenylsilanediol or a para-substituted diphenylsilanediol derivative.

4. The preparation method according to claim 1, characterized in that, In step (2), a catalyst is added to the reaction. The catalyst is at least one of organotin catalyst or titanate catalyst. The amount of catalyst used is 0.05% to 0.5% of the sum of the mass of tetraethyl orthosilicate and diarylsilanediol in step (2).

5. The preparation method according to claim 1, characterized in that, In the preparation process of the waterborne organosilicon resin, the total amount of raw materials added, in molar parts, is as follows: the amount of tetraethyl orthosilicate added is 10-30 parts, the amount of diarylsilanediol added is 20-50 parts, the amount of methyltriethoxysilane added is 30-60 parts, and the amount of hydrophilic silane monomer added is 10-25 parts.

6. The preparation method according to claim 1, characterized in that, In step (3), the acid is glacial acetic acid or formic acid.

7. The preparation method according to claim 1, characterized in that, In step (4), the temperature of the vacuum distillation is 40~60℃ and the vacuum degree is -0.08~-0.095 MPa; the temperature is reduced to 20~30℃; the speed of the high-speed shear stirring is 1200~2500 r / min.

8. An aqueous organosilicon resin prepared by the preparation method according to any one of claims 1 to 7.

9. A method for preparing a water-resistant coating using the water-based organosilicon resin according to claim 8, characterized in that: The water-based silicone resin is coated onto the surface of the substrate, and after surface drying at room temperature, it is cured at 150~180℃ for 20~40 minutes to obtain a water-resistant coating.

Citation Information

Patent Citations

  • Preparation method of high-modulus potassium silicate inorganic nano-resin

    CN103421368A